Methods error diagnoses in thyroid pathology - Delgado, Bolívar (Cirugía del Uruguay, 1992)
The authors evaluate and compare the following methods' capability to determine the anatomical pattern of the thyroid in a series of 205 patients operated with anatomopathological control: c/inic, cytological puncture, gammagram, and echography. They emphasize the c/inic's high value and the lesser one of the paraclinical exams, either single or associated, particular/y echography.